Novel lead - free relaxor ferroelectric based on Mg1-xSrxTiO3 (MTO:Sr) nanostructured for radar absorbing applications - Dere, A. (Elsevier Science Sa, 2019)
Novel relaxor ferroelectric based electromagnetic wave shielding at microwave frequency materials, containing Sr doped MgTiO3, were developed and investigated. The structural and morphological characteristics of the products were analyzed using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The samples were found to sensitive to Sr doping level and the presence of Sr was confirmed. The optical band gap of pure MgTiO3, 1% Sr doped, 3% Sr doped and 5% Sr doped MgTiO3 was estimated to be 3.75, 4.02, 4.06 and 4.10 eV, respectively. The microwave dielectric properties of Sr-doped MgTiO3 as a function of microwave frequency in the range of 1-20 GHz were examined. With Sr - doping, the microwave dielectric properties of the MgTiO3 is improved considerably. The applicability of as fabricated Sr doped MgTiO3 for electromagnetic wave shielding effectiveness at microwave frequency was studied. The dependence of the polarization of MgTiO3 as a function of Sr content was examined in details. This makes the Sr doped MgTiO3 good candidates for uses as high permittivity materials and it will be versatile for various electromagnetic wave shielding applications at microwave frequency. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Perovskite nanoparticles; Optical properties; Dielectric properties; Ferroelectric